Correction: Public preferences for ecological indicators used in Everglades restoration - Stainback, G. Andrew; Lai, John H.; Pienaar, Elizabeth F.; Adams, Damian C.; Wiederholt, Ruscena; Vorseth, Chloe’ (PloS one, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0234051.].